Rationalization of excise tax on distilled spirits: Balancing national objective and international relations in promoting fair trade - Javier, Maria Feliza Amparo Christina S. (Animo Repository, 2011)
Globalization has brought many advantages and disadvantages to different States. One advantage is the exchange of goods between countries. Free and fair trade allowed countries to develop their economies by expanding to the global market. In free exchange, barriers to trade such as tariffs and internal taxes are eliminated or at least minimized. However, countries which enter into trade agreements with other countries must conform with the standards that are provided therein. Disputes among countries have risen due to the conflicts between international agreements on trade and internal taxes. WTO cases such as Japan – Custom Duties, Taxes and Labelling Practices on Imported Wines and Alcoholic Beverages, Korea – Taxes on Alcoholic Beverages, and Chile – Alcoholic Beverages have provided areas of potential conflict on whether or not internal taxes on distilled spirits are in violation of the National Treatment Principle under the rules on international trade. This study attempts to develop a framework that will help us understand the relation between international trade and excise taxation. It is in this context that this study will examine whether or not the Philippine excise tax system on distilled spirits conforms with our obligations under our international trade agreement. After evaluating the current tax system, the goal is to formulate what will constitute the appropriate and neutral tax policy in line with our international trade agreement.